Examining the Role of Islamic Education Teachers in Fostering Good Character Among Students at Al-Fityah Integrated Islamic Junior High School in Pekanbaru - Darmansyah, Darmansyah; Aprita, Junia; Putri, Apriliana; Novitasari, Shinta; Naufal, Naufal; Amsar Harahap, Rafi; Muslim, Rafli Efendi (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2026)
This study aims to determine the strategies used by Islamic Religious Education teachers in fostering good character at SMP IT Al Fityah in Pekanbaru. Specifically, it seeks to examine the character-building efforts undertaken by Islamic Religious Education teachers at SMP IT Al Fityah in Pekanbaru. The method used in this study is a descriptive method employing a qualitative approach. Data collection procedures involved observation, interviews, and documentation. The interviews in this study were conducted with Islamic Religious Education teachers. The data analysis process used in this study included data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that Islamic Religious Education teachers have implemented various effective strategies to strengthen students’ akhlakul karimah. These strategies include fostering religious practices, providing guidance, and consistently modeling exemplary behavior in daily school activities. The implementation of these strategies has proven to have a positive impact on changes in students’ religious attitudes and behaviors. These findings underscore that structured and sustained character development is crucial in supporting the success of character education.